A Literature Review on the Implementation of Deep Learning Approaches in Al-Assisted Education - Indrianingsi, Agung; Winarni, Winarni; Insantuan, Balthasar; Bulung, Rensi; Rissi, Andrie Riomalen Yorda; Sinaga, Demeria (Asian Journal of Applied Education (AJAE), 2025)
The advancement of digital technology and artificial intelligence (AI) has brought significant transformation to the field of education, particularly in the implementation of deep learning approaches. This study aims to review various literature sources on the integration of AI in deep learning to create learning experiences that are more personalized, adaptive, efficient, and inclusive. Through a literature review of scholarly sources, this study identifies several AI applications such as chatbots, content recommendation systems, automated assessments, language learning apps, and learning analytics that support the core principles of deep learning: mindfulness, meaningfulness, and joyfulness. The findings indicate that AI can enhance student motivation, provide real-time feedback, and respond to individual learning needs. However, challenges remain in terms of data privacy, technological access gaps, and ethical considerations. Therefore, effective implementation strategies, teacher competency development, and inclusive policies are essential for the successful adoption of AI-based deep learning. This study offers practical insights for educators and policymakers to optimize the potential of AI in improving the quality of education in the digital era.